Lawyers in the Bazaar: Challenges and Opportunities for Open Source Legal Communities (Journal of Open Law, Technology & Society, 2010)
There is a fairly common perception among members of the Free and Open Source software (FOSS) developer community that there is no equivalent community of FOSS lawyers. Despite that perception, the FOSS legal community exists and is growing. This note will explore the gap between the perception and the reality, first by briefly surveying the state of the FOSS legal community, and then by exploring the reasons why there is such a disconnect between the lawyers and the community of our clients. Finally, it will suggest some ways in which this nascent community might invest in improving itself.